2020
DOI: 10.5296/jas.v8i2.16602
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus Between Agriculture and Tourism in the Island of Crete, Greece

Abstract: The relationship between agriculture and tourism in the island of Crete, Greece has been studied. Both agriculture and the tourism industry contribute more than 50% in the Gross Domestic Product of the island. The linkages between agriculture and tourism in many tourism-dominated communities and rural areas worldwide have been reviewed. The current status of agriculture and the tourism industry in Crete has been examined as well as the agro-tourism development in the island during the last few decades which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Hotels can be competitive when they respond to the increased demand for tourism experiences linked to the "taste of place" [12,14,32] and the strategy they implement is important for such a purpose [2,28]. Moreover, tourists' stay can be strongly linked to food, since in hotels, tourists are usually in daily contact with local agri-food products [1,2,4,6,14,28] and when they return to their countries, they are likely to seek them out [4,45]. Therefore, enhancing the dynamic involvement of hotels in promoting gastronomy tourism can be beneficial for the destination [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hotels can be competitive when they respond to the increased demand for tourism experiences linked to the "taste of place" [12,14,32] and the strategy they implement is important for such a purpose [2,28]. Moreover, tourists' stay can be strongly linked to food, since in hotels, tourists are usually in daily contact with local agri-food products [1,2,4,6,14,28] and when they return to their countries, they are likely to seek them out [4,45]. Therefore, enhancing the dynamic involvement of hotels in promoting gastronomy tourism can be beneficial for the destination [31].…”
Section: Discussionmentioning
confidence: 99%
“…The latter blunts the price gap in local agri-food products due to the limited involvement of intermediaries, as other studies have observed [1,3,5,29]. To address this problem, local actors have to play a coordinating role to mitigate the differences between stakeholders and strengthen the supply network [6]. Furthermore, certifying the quality of local agri-food products and joining certification networks can substantially help in this direction as well [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also destinations (e.g. Bosnia and Herzegovina, Croatia, Greece) who are now beginning to promote their gastronomic offerings (Fox, 2007; Meller and Cerovic, 2003; Peštek and Činjarević, 2014; Vourdoubas, 2020). This is particularly important for tourists who view a destinations’ gastronomy as an opportunity to experience something new, novel and adventurous (Lee and Crompton, 1992; Ji et al , 2016).…”
Section: Introductionmentioning
confidence: 99%